Medical emergency response in Islamic community: collaboration with network of mosque leveraging the whole concept of government and quadruple helix model in Malaysia - Hassan, Muhamad Hairulnizam; Muhammad, Gul; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2014)
A medical emergency is a situation where injury or illness that will discriminate grows an instant risk to a person's long-term health or even life. Eliminating the medical emergency has become the more critical issue in developed countries especially in rural areas and urban areas. The issues that are normally raised within the matter are on the reachability to the incident and also the time taken to respond to the incident. In this paper we discussed how the Islamic Community with the help of the Whole-of-Government concept (WoG) and Quadruple Helix Model (QHM)together with the concept of Network of Mosque (NoM) will help the congested area where ambulance or medical assistance hard to reach in case of accident, or health Emergency. The Authors intended a consolidative and cooperative mechanism of Mosque and Knowledge Management (KM) as to facilitate the emergency response to the victims. By leveraging on the above concepts, writers empathize that the Medical Emergency can be further effaced in rural areas in Malaysia.